Assessment of Acoustic Emission and Triaxial Mechanical Properties of Rock-Cemented Tailings Matrix Composites - Shuai Cao; Erol Yilmaz; Weidong Song; Gaili Xue (Advances in Materials Science and Engineering)
Acoustic emission (AE) test is a powerful technique for examining the sounds of cracks growing, breaking, and other modes of damage in cementitious materials deforming under stress, such as rock-cemented tailings matrix composites (RCTMC). RCTMC, an engineered mixture of tailings, cement, rock, and water, is widely used to fulfill numerous important roles at underground mine sites as a construction material and a ground support tool. To study the mechanical strength and AE properties of RCTMC, compression testing was carried out using a triaxial compression test system (TAW-2000) and AE monitoring system (PCI-2), and the failure modes of samples were also examined. Results have shown that (1) the failure process of RCTMC samples can be divided into six main stages: compaction, linear elastic characteristic, crack growth, primary damage development, cemented tailings backfill withstand stress zone, and secondary damage development stage. CTB has the strengthening effect on mechanical strength of rock; (2) the AE process can be also divided into six main stages: the prepeak quiescence period, the elastic energy reserve period, the first destruction development AE area, the secondary energy reserve period, the second damage development stage, and the postpeak calm period; and (3) samples’ cumulative ring count is “stepped” distribution over time, and the ring count has entered the postpeak flat stage after many active periods. The process of RCTMC samples from tensile to shear failure mode is represented by numerical simulation. Finally, the obtained experimental results can offer a useful reference for the further study of the mechanism of the surrounding rock and cemented tailings backfill structure.